2014
DOI: 10.1007/s00265-013-1681-8
|View full text |Cite
|
Sign up to set email alerts
|

Phaeomelanin- and carotenoid-based pigmentation reflect oxidative status in two populations of the yellow warbler (Setophaga petechia)

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag Berlin Heidelberg. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…The following exclusion criteria were applied: i) studies that measured expression of antioxidant genes because I were interested in the biochemical differences between sexes; ii) studies that used metrics of free radical generation as an index of oxidative stress, since they do not provide direct evidence of oxidative stress (reactive species might be mopped up before oxidative damage is generated); iii) studies where necessary information for calculating effect size was unavailable. Overall, the final dataset included 732 effect sizes from 100 articles (82 species: 7 fish, 5 reptiles, 44 birds, and 26 mammals) (Almroth et al 2008; Alonso-Alvarez et al 2004a, 2004b; Barrera-García et al 2012; Beamonte-Barrientos and Verhulst 2013; Beaulieu and Schaefer 2014, Beaulieu et al 2010, 2011, 2014; Bertrand et al 2006; Bilham et al 2013; Bize et al 2008; Bonisoli-Alquati et al 2010; Canovas et al 2014; Casagrande et al 2011, 2012a, 2012b; Cecere et al 2016; Christensen et al 2015; Christie et al 2012; Cohen et al 2008; Costantini and Bonadonna 2010; Costantini and Dell’omo 2015; Costantini et al 2007, 2008, 2010, 2012a, 2012b, 2013, 2014, 2014a, 2014b; Costantini 2010; Cram et al 2015a, 2015b; Depboylu et al 2013; Ehrenbrink et al 2006; Emaresi et al 2016; Figueiredo-Fernandes et al 2006b; Georgiev et al 2015; Gomes et al 2014; Grunst et al 2014; Heiss and Schoech 2012; Herrera-Dueñnas et al 2014; Isaksson et al 2009, 2011, 2013; Isaksson 2013; Jolly et al 2012; Kamper et al 2009; Kanerva et al 2012; Kayali et al 2007; Kurhalyuk et al 2009; Langley-Evans and Sculley 2005; Leclaire et al 2015; Lilley et al 2014; Lopes...…”
Section: Methodsmentioning
confidence: 99%
“…The following exclusion criteria were applied: i) studies that measured expression of antioxidant genes because I were interested in the biochemical differences between sexes; ii) studies that used metrics of free radical generation as an index of oxidative stress, since they do not provide direct evidence of oxidative stress (reactive species might be mopped up before oxidative damage is generated); iii) studies where necessary information for calculating effect size was unavailable. Overall, the final dataset included 732 effect sizes from 100 articles (82 species: 7 fish, 5 reptiles, 44 birds, and 26 mammals) (Almroth et al 2008; Alonso-Alvarez et al 2004a, 2004b; Barrera-García et al 2012; Beamonte-Barrientos and Verhulst 2013; Beaulieu and Schaefer 2014, Beaulieu et al 2010, 2011, 2014; Bertrand et al 2006; Bilham et al 2013; Bize et al 2008; Bonisoli-Alquati et al 2010; Canovas et al 2014; Casagrande et al 2011, 2012a, 2012b; Cecere et al 2016; Christensen et al 2015; Christie et al 2012; Cohen et al 2008; Costantini and Bonadonna 2010; Costantini and Dell’omo 2015; Costantini et al 2007, 2008, 2010, 2012a, 2012b, 2013, 2014, 2014a, 2014b; Costantini 2010; Cram et al 2015a, 2015b; Depboylu et al 2013; Ehrenbrink et al 2006; Emaresi et al 2016; Figueiredo-Fernandes et al 2006b; Georgiev et al 2015; Gomes et al 2014; Grunst et al 2014; Heiss and Schoech 2012; Herrera-Dueñnas et al 2014; Isaksson et al 2009, 2011, 2013; Isaksson 2013; Jolly et al 2012; Kamper et al 2009; Kanerva et al 2012; Kayali et al 2007; Kurhalyuk et al 2009; Langley-Evans and Sculley 2005; Leclaire et al 2015; Lilley et al 2014; Lopes...…”
Section: Methodsmentioning
confidence: 99%
“…However, we also predicted that highly pigmented males might be more likely to maintain provisioning effort at concealed nests, in accordance with results. In our population, carotenoid pigmentation increases longitudinally with male age (Grunst et al , ), and is greater in first year breeding males that are in better condition as nestlings and at pre‐breeding molt (Grunst et al ). Thus, carotenoid‐based pigmentation may be related to quality and age‐related differences in both the ability to evade predation, and experience with assessing predation threats (Cabido et al , Fowler‐Finn and Hebets ).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the two pigment types may convey non‐equivalent information (Grunst et al ). We have previously established that carotenoid‐ and phaeomelanin‐based pigmentation are associated with metrics of individual condition in both sexes of the yellow warbler (Grunst et al , ), and warblers show assortative social pairing by pigmentation (Grunst and Grunst ). Further, a past study found greater extra‐pair paternity among males expressing more melanin‐based pigmentation (Yezerinac and Weatherhead ), and in our study population males co‐expressing high levels of both melanin‐ and carotenoid‐based pigmentation lose less paternity in their social broods (Grunst and Grunst ).…”
mentioning
confidence: 99%
“…Red chroma was calculated as the proportion of reflectance in the red range of the spectrum (600–700 nm) to the total reflectance at 300–700 nm (S1R in rclr software; Montgomerie ), and it was used to characterize saturation of pheomelanin‐based coloration (Grunst et al . , Zduniak et al . ).…”
Section: Methodsmentioning
confidence: 99%